THE IMPERATIVE OF REFORMS IN TEACHING FOREIGN LANGUAGES TO ADULTS: A METHODOLOGICAL NECESSITY AND SOCIAL TREND - Rudnyeva, Iryna; Kobrynets, Olga; Chub, Victoria; Lysenko, Natalya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This article studies the imperative of reforms in teaching foreign languages to adults both from the social point of view and methodological needs of the particular process of foreign language teaching for representatives of a special age group. The starting point of the article is the authors` own experimental research in the form of a questionnaire, which, as the target audience, conducted a survey of people aged 45+ studying at or graduated from foreign language courses as a part of integration programs (the survey was conducted among relocants from Ukraine after February 24, 2022) finding out what factors contributed / did not contribute to their success and psychological comfort in language learning. The second part of the study presents the results of a survey of teachers who work in foreign language courses attached to higher educational institutions of Ukraine and presents their point of view on the difficulties of teaching in mixed age groups and in groups dominated by people over 40 years. The purpose of the article is to show that in order to fulfill the social tasks that modern society places on the study of foreign languages by older people, changes in methodological approaches to the stated process are necessary.